The demand for transport and logistics services in the Friuli Venezia Giulia Region - Danielis, Romeo (Array, 2007)
The paper reports on a research carried on in April 2007 on a sample of manufacturing firms in the Friuli Venezia Giulia Region, Italy. The aim was to understand the nature and the prospects of the transport and logistics demand deriving from firms. It resulted that firms require an intense and growing amount of services to procure inputs and deliver products to a large number of destination, both nationally and internationally. A large percentage of the shipments is full load, point-to-point shipments which require traditional transport operators. However, there is a growing share of shipments which demand groupage\courier services implying logistics operators able to make higher levels of investments, manage a national or international network, exploit scale and scope economies and compete in quality and not only in costs